2018
DOI: 10.1111/tid.12907
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mTOR inhibitors on the incidence of CMV infection in high‐risk donor positive–recipient negative (D+/R−) kidney transplant recipients

Abstract: In this cohort of high-risk CMV D+/R- kidney transplant recipients receiving rATG induction and tacrolimus, the use of mTOR inhibitors could only show a tendency towards but not a significant difference on the incidence of CMV events, when compared to antimetabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Consistent with previous studies, the EVR + rCNI regimen offered significant protection from viral infections up to 24 months, thereby confirming the antiviral effect of EVR even in the presence of TAC levels above target range. Of interest, the CMV incidence was also significantly lower with EVR + rCNI in high‐risk (D+/R−) patients.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with previous studies, the EVR + rCNI regimen offered significant protection from viral infections up to 24 months, thereby confirming the antiviral effect of EVR even in the presence of TAC levels above target range. Of interest, the CMV incidence was also significantly lower with EVR + rCNI in high‐risk (D+/R−) patients.…”
Section: Discussionmentioning
confidence: 98%
“…Among the D+/R− combination, the overall incidence of CMV infection was 46% using only preemptive treatment. The lower efficacy of mTORi for the prevention of CMV infection/disease in this high‐risk group has been previously reported even in patients receiving mTORi, and the lack of specific anti‐CMV cellular immunity appears to be involved . A comprehensive and elegant study showed that sirolimus significantly improved CMV‐specific effector memory T‐cell function and negatively influenced naïve T cells …”
Section: Discussionmentioning
confidence: 85%
“…However, in an intermediate risk situation, these drugs might shift the balance toward the control. The magnitude of the mTORi effect may be associated with the presence of CMV‐specific memory cells . To note, the small sample size does not allow us to drawn definitive conclusions about it.…”
Section: Discussionmentioning
confidence: 94%